For a living and healthy Panamazonia: the perspective of Good Living (PerCursos, 2022)
This article analyzes some of the consequences that a perspective of economic growth through the dominance of what are often referred to as "natural resources" has for the Amazon region and its socio-biodiversity. Through a critical analysis of recent academic literature and journalistic articles, it aims to contextualize the Amazon region and its importance for the planet, as well as to show the extent of the problem of deforestation and to point out some of its consequences. As a counterpoint to the "exploitation of nature" promoted by the capitalist system, which only benefits a minority of human beings to the detriment of a majority of other beings - human and non-human - and their environments, the cosmovision of Good Living developed by the Andean-Amazonian peoples and the decolonial perspective are highlighted. Good Living defends the need to respect all forms of life. Thus, it constitutes a possibility of establishing another relationship between all living beings and their environments and, as a consequence, an attempt to avoid the destruction of what is left of the Amazon rainforest and the possible appearance of other pandemics similar to that of COVID-19 in that region.
Keywords: good living; anthropocentric paradigm; coloniality; Amazon rainforest; COVID-19 pandemic